2023
DOI: 10.3390/polym16010129
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Gelatin Coating and GO Incorporation on the Properties and Degradability of Electrospun PCL Scaffolds for Bone Tissue Regeneration

Carlos Loyo,
Alexander Cordoba,
Humberto Palza
et al.

Abstract: Polymer-based nanocomposites such as polycaprolactone/graphene oxide (PCL/GO) have emerged as alternatives for bone tissue engineering (BTE) applications. The objective of this research was to investigate the impact of a gelatin (Gt) coating on the degradability and different properties of PCL nanofibrous scaffolds fabricated by an electrospinning technique with 1 and 2 wt% GO. Uniform PCL/GO fibers were obtained with a beadless structure and rough surface. PCL/GO scaffolds exhibited an increase in their cryst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 89 publications
1
5
0
Order By: Relevance
“…PCL nanofibers manufactured with nHAp presented the highest (22.7%) post-analysis residue compared with the PCL alone and PCL/nHAp/hop samples (0.835% and 19.19%, respectively). In this study, PCL presented a residue of less than 1%, as observed previously [46]. The degradation curves of the analyzed samples are presented in Figure 2.…”
Section: Thermogravimetric Analysis (Tga)supporting
confidence: 84%
“…PCL nanofibers manufactured with nHAp presented the highest (22.7%) post-analysis residue compared with the PCL alone and PCL/nHAp/hop samples (0.835% and 19.19%, respectively). In this study, PCL presented a residue of less than 1%, as observed previously [46]. The degradation curves of the analyzed samples are presented in Figure 2.…”
Section: Thermogravimetric Analysis (Tga)supporting
confidence: 84%
“…Gel NPs have been widely used as drug and gene carriers and could be a valid candidate for novel BTE applications due to their low toxicity and cost-effectiveness, as well as their great bioactivity and biodegradability [102]. In their in vitro study, Loyo et al reported a synergic effect of gel and graphene oxide (GO) NPs, enhancing the multifunctionality of a polycaprolactone (PCL) nanofibrous scaffold in terms of the degradability rate, bioactivity, and cell adhesion and proliferation of human gingival mesenchymal stem cells (hGMSC cells), making it an interesting biomaterial for BTE applications [103].…”
Section: Natural Polymersmentioning
confidence: 99%
“…A direct contact assay of human foreskin fibroblasts (HFF-1) on PCL fibrous scaffolds enriched with different percentages of GO demonstrated an irregular porosity proportional to the increase in GO content and that the scaffolds were able to promote the adhesion and spreading of eukaryotic cells, for up to 14 days of incubation [ 8 ]. Additionally, in another study, the researchers demonstrated that the GO presence (1% or 2%) in PCL-based scaffolds permitted human cell adhesion and proliferation even though at a lower rate compared to pure PCL [ 15 ].…”
Section: Cytocompatibility Of Pcl-based Biomaterials Functionalised W...mentioning
confidence: 99%
“…Notably, several studies have demonstrated that enriching PCL with natural polymers, such as chitosan and gelatin, further enhances human cell adhesion and proliferation by providing cues for these cells. This increase is attributed to the enhancement in surface and bulk hydrophilicity [10,[14][15][16]. Several review articles have focused on the use of PCL in tissue engineering; however, to the best of our knowledge, none have specifically addressed bone tissue engineering.…”
Section: R Peer Review 3 Of 39mentioning
confidence: 99%
See 1 more Smart Citation